Austerity, Women and the Role of the State : Lived Experiences of the Crisis - Dabrowski, Vicki (Book collections on Project MUSE., 2021)
Delivering a timely account of the misconceptions of policies, discourses and representations around austerity in the UK, Dabrowski illustrates the complex ways through which austerity is experienced by women in their everyday lives.